Dose Response and Pharmacokinetics of Tofacitinib (CP‐690, 550), an Oral Janus Kinase Inhibitor, in the Treatment of Chronic Plaque Psoriasis. (22nd May 2013) - Tan, H; Gupta, P; Harness, J; Wolk, R; Chapel, S; Menter, A; Strober, B; Langley, RG; Krishnaswami, S; Papp, KA
Abstract : Longitudinal nonlinear mixed effects modeling was used to characterize the dose–response profile of tofacitinib using data from a placebo‐controlled dose‐ranging study, where tofacitinib 2, 5, and 15 mg twice daily (b.i.d.) were evaluated for plaque psoriasis treatment. Bayesian estimation was applied with prior information derived from the literature: nonclinical and clinical data in psoriasis, as well as other indications. The probability to achieve a certain target effect associated with a given dose was calculated from the posterior samples. On the basis of these probabilities along with safety considerations, tofacitinib 5 and 10 mg b.i.d. were selected for further testing in confirmatory phase III clinical trials. Pharmacokinetics in patients with psoriasis was characterized using a population‐based modeling approach, and body weight was identified as an important covariate. A subgroup analysis suggested reduced efficacy of tofacitinib with increasing body weight; however, it is unclear whether this trend could be explained by systemic exposure alone. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e44; doi:10.1038/psp.2013.22 ; advance online publication 22 May 2013